Analysis of Regional Tax Potential of Pamekasan Regency - Anggoro, Damas Dwi; Indriani, Indriani; Wilopo, Wilopo (UI Scholars Hub, 2022)
Fiscal decentralization is a critical element in the implementation of regional autonomy where the central government gives authority to local governments to manage their finances independently. Pamekasan regency is one of the region that has succeeded in increasing the ratio of local own-source revenue (Pendapatan Asli Daerah/PAD) by rising the potential of its regional tax sector. However, several problems arising may cause inaccuracies in collecting local tax revenues. This study aims to analyze the potential loss of local taxes in Pamekasan regency. A qualitative approach sourced from primary data (interviews or filling the questionnaires) and secondary data (obtained and recorded by other parties, secondary data are the realization of Pamekasan Regency's original revenue) was adopted in this study. Results showed several potential tax leakages have occurred in Pamekasan regency with tax gap of 43% was sourced from total hotel tax revenue realization, 60.4% of total restaurant tax realization, 86% of total entertainment tax realization, 81% of total parking tax realization, and 32% of the total in groundwater tax realization. This study provides several policy recommendations for local governments to increase the potential for local tax revenues in the future.